Neoarchean high-pressure granulite-facies anatexis of continental rocks in the Belomorian Eclogite Province, Russia - Dokukina, K. A.; Khiller, V. V.; Khubanov, V. B.; Mints, M. V.; Dokukin, P. A.; Natapov, Lev; Belousova, Elena; Yakushik, M. A. (Precambrian Research, 2022)
Eclogites exposed along the northeastern boundary of the Belomorian orogen in the eastern Fennoscandian Shield formed as a result of Mesoarchean–Neoarchean subduction. Highly-deformed banded TTG gneisses with eclogitized mafic pods, lenses and dykes in the Gridino association of metamorphic rocks have been modified locally to have typical migmatite structures that formed as HP rocks decompressed through HP granulite-facies metamorphic conditions (16–12 kbar, 800–850 °C) to amphibolite-facies conditions (10–9 kbar, 600–700 °C). The migmatites are located with the boundaries between felsic and mafic lithologies, which are the most suitable place for partial melting, fluid migration, and component diffusion. Symplectic intergrowths of hydrous minerals (mica, epidote) together with quartz in the leucosome are important markers of arrested reaction textures that formed by reversed hydration crystallization of residual melts or by fluids where their infiltrated through migmatite areas. There are two potassic granitic leucosomes with contrasting geochemical signatures. Garnet and phengite-bearing leucosome replaces the host TTG gneiss and percolates mafic rocks. This leucosome is distinguished by a high Ba content, striking positive Eu and Sr anomalies and corresponding low concentrations of all other trace elements. The compositions of the leucosome record initial segregation and migration of melt away from the residual source and subsequent crystal fractionation, dominated by feldspars, of the escaped melt. Migration of anatectic melts led to the formation of small bodies of leucogranite that are characterized by high contents of trace elements and negative Eu and Sr anomalies. Leucogranites formed from portions of fractionated melt that percolated the migmatites and solidified. Anatexis occurred during the Neoarchean time (∼2.7 Ga). U-rich zircon domains were partly or completely affected by radiation damage that yield discordant scattered dates between 2.7 and 1.9 Ga, which are interpreted as reflecting a thermal ...